2023
DOI: 10.3389/fnagi.2023.1087318
|View full text |Cite
|
Sign up to set email alerts
|

A novel digital biomarker of sarcopenia in frail elderly: New combination of gait parameters under dual-task walking

Abstract: BackgroundFrailty caused by deterioration in multiple physiological systems has led to a significant increase in adverse events such as falls, disability, and death in frail older people. Similar to frailty, sarcopenia, defined as loss of skeletal muscle mass and strength, is tightly related to mobility disorders, falls, and fractures. With population aging, co-occurrences of frailty and sarcopenia are increasingly common in the elderly, which are more deleterious for the health and independence of older adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…All included studies reported results for lower limb functional indicators, such as gait speed, turn duration, step length and step frequency; and two of the studies [24,29] presented gait indicator results by reporting dual-task costs (DTCs). The results of four studies [23,25,27,28] showed that DT testing significantly worsens gait performance in frail older adults; and both the studies by Piche et al and Zheng et al showed that the DTC of gait was significantly higher in the frail population [24,29]. Cognitive function outcomes were reported in two studies; and the indicators chosen were call accuracy and counting accuracy.…”
Section: Conceptual Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…All included studies reported results for lower limb functional indicators, such as gait speed, turn duration, step length and step frequency; and two of the studies [24,29] presented gait indicator results by reporting dual-task costs (DTCs). The results of four studies [23,25,27,28] showed that DT testing significantly worsens gait performance in frail older adults; and both the studies by Piche et al and Zheng et al showed that the DTC of gait was significantly higher in the frail population [24,29]. Cognitive function outcomes were reported in two studies; and the indicators chosen were call accuracy and counting accuracy.…”
Section: Conceptual Descriptionmentioning
confidence: 99%
“…All studies [23][24][25][26][27][28][29] reporting MT testing in the frail elderly population used the DT mode; with seven studies using the cognitive-motor DT mode, including a walking task while performing a counting task, walking while talking or naming an animal, etc. ; and one study [29] additionally selecting the moto-motor DT mode (walking while holding a glass of water).…”
Section: Conceptual Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kang et al [ 28 ] found sarcopenic elderly men walked significantly slower daily than non-sarcopenic peers. Dual-task assessments demonstrate greater slowing in individuals with sarcopenia versus single-task walking [ 29 ]. Greater dual-task costs are associated with increased fall risks and mobility impairment.…”
Section: Physical Performance Test For Sarcopeniamentioning
confidence: 99%
“…Kang et al [ 28 ] showed daily gait speed derived from wearables accurately reflected sarcopenia diagnosis. Machine learning models using combinations of gait features derived from wearables may enable sarcopenia detection and monitoring [ 29 ]. Compared to infrequent clinical gait tests, continuous monitoring could facilitate early identification of mobility decline.…”
Section: Physical Performance Test For Sarcopeniamentioning
confidence: 99%